KEDUDUKAN DAN STRATEGI HUKUM ISLAM DALAM POSITIVISASI HUKUM DI INDONESIA - Muhammad Shohibul Itmam; Luluk Sekar Liyana (Program Studi Hukum Keluarga Islam, 2019)
Islamic law in the context of its position and strategy towards national law into positive law has sparked controversial sustainability since independence until now. The various strategies and explanations about them give a special pattern to the specificity of Islamic legal thinking in Indonesia. This paper focuses on how the position and strategy of Islamic law in legal positivity in Indonesia. With the legal normative and sociological approach of jurisprudence, this paper confirms a conclusion that the position of Islamic law becomes part of the raw material of national law that can be managed in a pluralist manner in conjunction with other laws that grow in Indonesia. Plurality of Indonesian law which is a necessity to be a positive partner for Islamic law towards positivation of legal law nationally. The strategy carried out is by uniting perceptions which are the substance of the teachings of Islamic teachings in the meaning of Shari'a and fiqh in the form of values of universality that exist in Islam such as the substance of justice, honesty, equality of balance and the like. With such a position and strategy of Islamic law can provide a solution as well as a great opportunity for Indonesian Islamic law to move in to color the development of national law into positive law through the process of positivist Islamic law in Indonesia.